Herpes simplex virus immediate-early promoters are responsive to virus and cell trans-acting factors. - Gelman, I H (1987)
The promoters for each of the immediate-early genes from herpes simplex virus type 1 were cloned and fused to a chloramphenicol acetyltransferase cassette. These chimeric genes were used as targets in a transient expression assay to determine how the immediate-early gene products ICP4 and ICP0 and the virion-associated stimulatory protein Vmw65 affected their expression in HeLa and Vero cells. The basal level of expression from these cassettes differed significantly depending on the extent of 5'-flanking sequence and the cell line that served as host. The promoters from IE-4 and IE-0 behaved in a qualitatively similar fashion independent of the host cell. However, the promoter for ICP27 had a unique response pattern: in Vero cells it acted as an alpha gene promoter, whereas in HeLa cells its response was more like that of a beta gene promoter. The promoter sequences for ICP22 and ICP47 behaved as the IE-4 and IE-0 promoters did in HeLa cells, but their response to the effector molecules in Vero cells was unlike that of other alpha gene promoters we have studied. Evidence is also presented for a role for ICP27 in autoregulation.